NADZIR REGISTRATION REGULATION TO THE INDONESIAN WAQF BOARD WITH A POSITIVE LEGAL PERSPECTIVE AND ISLAMIC LAW - Muhammad Luthfi; Yohana Wardoyo (Universitas Muhammadiyah Ponorogo, 2020)
Regulation of nadzir registration to Indonesian Waqf Agency (BWI) is a new rule about Waqf in Indonesia. This rule has a different push point in the rules, the rule of law using the word